Care for Bosnia and Herzegovina war disabled during the First World War (1914–1918) - Užičanin, Salkan (Historical Thought, 2024)
The paper analyzes the state’s and society’s concern for Bosnian war invalids during the First World War. In particular, they point to the fact that initially the organization of care for war invalids encountered serious organizational and material problems, because there were no institutions and facilities for that purpose in the country. The weakly developed network of health institutions, in terms of personnel and space, was taken aback by the sudden influx of wounded and sick soldiers returning from the battlefield. Certain types of disea ses, such as tuberculosis and some other Bosnian diseases, could not be adequately treated by the domestic health system even until the end of the war. The main task of the authori ties in the beginning was treatment, and later the range of care for the wounded and sick was significantly expanded. They especially tried to provide social care for the disabled, and then institutions were established for their rehabilitation, retraini ng and training for selfemployment. Special governmental institutions established during the war, as well as the nongovernmental sector, worked on this.